Change in the Oxide Structure of Al-12Si Melts in the Presence of Sr - Kahruman, Cem; Alev, Ugur; Dispinar, Derya (My University, 2023)
Bifilm defects are the surface entrained double oxide films that are introduced into melts during turbulence and disturbance to the surface of the melt. These defects lead to porosity formation if they are not cleaned from the melt. Thus, the characterisation of the dross that is formed on the surface of the melt becomes a key parameter. In this work, Sr containing Al12Si alloy was used. For the modification process, 100, 200 and 300 ppm Sr was added to the alloy. The oxidation tests were carried out in liquid state at 700, 750 and 800 °C for holding durations of 12, 24, 36 and 48 hours. The structure was characterised by optical microscopy, Scanning Electron Microscopy, X-Ray Diffraction and X-ray photoelectron spectroscopy techniques. It was found that after 12 hours of holding, spinel oxides were formed on the surface mainly SrO.Al2O3 and MgO.Al2O3.
Keywords: XPS; Strontium modification; Al-12Si; oxide films